PROFIL LEVEL KONTEKS PADA SOAL MODEL PISA - Wardani, Ambarsari Kusuma (HISTOGRAM: Jurnal Pendidikan Matematika, 2020)
One of the obstacles in designing the PISA like problems is determining the right context in order to make the questions make sense for students to solve. Therefore, this study aims to determine the profile of the context level in the PISA like problems developed by novice researchers, students of the Mathematics Education Study Program in one of university in Palembang, South Sumatra, who conducted a final assignment research on the topic of developing the PISA like problems. The level of context in this study is defined as a matter of mathematical models that use situations that are either found in the real world that make sense in students' understanding. Context level is divided into three, namely camouflage context, contexts that need solutions, and contexts that require mathematical models. Document observation was carried out to collect the profile data about the PISA model through filling in the checklist sheet and quantitative descriptions. The document observed in this activity was 43 items of PISA like problems from the four research subjects involved. Based on the results, it can be concluded that the PISA like problems developed by research subjects are still dominated by questions with a camouflage context that is equal to 53.49%. As many as 41.86% of the questions designed were already accompanied by contexts that needed solutions. However, the number of contexts requiring mathematical models is only 4.65%.